PENGARUH IMPLEMENTASI SISTEM FREEBALANCE PADA PENGALOKASIAN DANA CIVIL SOCIETY TERHADAP PENINGKATAN KUALITAS PELAYANAN PUBLIK - Carlito Gama (Universitas Tribhuwana Tunggadewi, 2015)
This study aimed to examine the effect of imlementasi system Freebalance in funds Civil Society on the quality of public services at the Directorate General of State Treasury of East Timor, to test the degree of influence the performance expectations of system implementation Freebalance to the expectations of the public service funds Civil Society, to test the degree of influence expectations of the business of implementation system Freebalance on the perception of public service funds Civil Society, to test the degree of influence of environmental conditions on the perception of public service funds Civil Society, to test the degree of influence jointly performance expectations, expectations of the business and the environmental conditions of the expectations of public services, to test the degree of influence the perception of public service funding Civil Society on the quality of public services, to test the effect of the level of expectations of public services to the quality of public services. This type of research using explanatory research (explanatory research) with quantitative approach. Samples taken are as many as 108 people and a random sample (random sampling) population of 147 people using the formula Yamane in Rachmat. By using hypothesis testing between independent variables with the dependent variable it can be seen that the performance expectations (X1) formed a direct and significant effect on the variable expectations of public services (Y1) with the value of the path coefficient of 0.417. Business expectation variable (X2) is formed direct and significant effect on the variable perceptions of service (Y2) with the value of the path coefficient of 0.42. Social environment variables (X3) formed a direct and significant effect on the variable perceptions of service (Y2) with the value of the path coefficient of 0.346. There is no direct influence between variable performance expectations (X1) via the service expectation variable (Y1) of 47.8%. This value is greater than the effect of indirectly between business expectations variable (X3) 39.6% and the social environment (X3) amounted to 35.4% through a service perception variable (Y2) amounted to 34.3%, still less than the direct effect between perceptions of service to service quality.